Axial Performance of Steel Piles in Sand and their Implications for Polymer-Based Coatings, Composite Strengthening, and Soil–Polymer Interaction Systems - Mohialden, Mufeed M.H.; Al-Gharrawi, Asaad M.B. (Journal of Research Updates in Polymer Science, 2025)
Polymer-based coatings, composite wraps, and functional polymer interfaces are increasingly used to enhance the durability and axial performance of steel piles in infrastructure applications. The establishment of baseline behavior of uncoated piles is a prerequisite for the design of integrated polymer systems. This paper presents an experimental comparison of the axial performance of H-section steel and closed-ended pipe piles embedded in poorly graded sand (SP) at 58% relative density. Eighteen static load tests were carried out on single piles and 2-pile and 4-pile groups using L/D ratios of 10 and 15. H-piles consistently demonstrated higher ultimate capacities because of soil plug formation, better interface shear mobilization, and densification during driving. Capacity gains with increasing L/D were as high as 109%, and up to 365% in H-pile groups. The test results establish a benchmark dataset for developing polymer-coated, polymer-modified, and FRP-strengthened pile systems and contribute to advances in polymer applications in geotechnical and infrastructure engineering.